Provenance and tectonic implications of Orán Group foreland basin sediments, Río Iruya canyon, NW Argentina (23° S) - Amidon, William H. (2017)
Foreland basins are important recorders of tectonic and climatic processes in evolving mountain ranges. The Río Iruya canyon of NW Argentina (23° S) exposes ca. 7500 m of Orán Group foreland basin sediments, spanning over 8 Myr of near continuous deposition in the Central Andes. This study presents a record of sedimentary provenance for the Iruya Section in the context of a revised stratigraphic chronology. We use U-Pb zircon ages from six interbedded ash layers and new magnetostratigraphy to constrain depositional ages in the section between 1.94 and 6.49 Ma, giving an average sedimentation rate of 0.93 ± 0.02 (2σ) km Myr−1. We then pair U-Pb detrital zircon dating with quartz trace-element analysis to track changes in sedimentary provenance from ca. 7.6 to 1.8 Ma. Results suggest that from ca. 7.6 to ca. 6.3 Ma, the Iruya watershed did not tap the Salta Group or Neogene volcanics that are currently exposed in the eastern Cordillera and Puna margin. One explanation is that a long-lived topographic barrier separated the eastern Puna from the foreland for much of the mid-late Miocene, and that the arrival of Jurassic-Neogene zircons records regional tectonic reactivation at ca. 6.3 Ma. A second major provenance shift at ca. 4 Ma is marked by changes in the zircon and quartz populations, which appear to be derived from a restricted source region in Proterozoic-Ordovician meta-sediments. Considered in conjunction with the onset of coarse conglomerate deposition, we attribute this shift to accelerated uplift of the Santa Victoria range, which currently defines the catchment's western limit. A third shift at ca. 2.3 Ma records an apparent disconnection of the Iruya with the eastern Puna, perhaps due to defeat of the proto Rio-Iruya by the rising Santa Victoria range. This study is one of the first applications of quartz trace-element provenance analysis, which we show to be an effective complement to U-Pb detrital zircon dating when appropriate statistical methods are applied.